Kekuasaan dan kepuasan pernikahan individu dalam pernikahan berpenghasilan ganda: Peran moderasi ideologi peran gender - Luh Ayu Candra Utami; Lathifah Hanum; Fivi Nurwianti; Cantyo Atindriyo Dannisworo (Jurnal Psikologi Ulayat, 2026)
Modernization in Indonesia increases the prevalence of dual-earner couples. Studies found mixed results on the relationship between marital power and marital satisfaction. In Indonesian society with a wide gender gap, it is interesting to examine gender role ideology as a potential moderator. This study aimed to examine the association between marital power process and marital power outcome on marital satisfaction, and the moderating role of gender role ideology. Participants were 227 dual-earner individuals (n women = 183 and n men = 44). Data was collected using CSI-16, MPI, and IPSPC, and data analysis was performed using simple moderation in Hayes PROCESS. Results showed that marital power process and marital power outcome positively predicted marital satisfaction, but there was no significant moderating effect of gender role ideology. The findings imply that regardless of gender role ideology, individuals in dual-earner marriage can achieve marital satisfaction when they perceive an equal level of influence within the marriage.